Compatibility of spectacles with their prescriptions in central Anatolia - Ilhan, Nilufer; Dogan, Hakki; Ilhan, Ozgur; Coskun, Mesut; Bulut, Betul Tasar; Ersekerci, Tulay Karacan (Seminars in ophthalmology, 2015)
To investigate compatibility of spectacles with their prescriptions. This study was conducted prospectively between October 2007 and March 2009. A total of 1002 spectacles of 1002 individuals were included in the study. First right and then left lenses of the spectacles were measured with a Topcon CL-200 digital lensmeter. Interpupillary distance (PD) of the subjects was measured. Spherical, cylindrical, and axial differences between the prescription and the spectacles were separately calculated for the left and right lenses. Prismatic effect (PE) of the lenses, with decentralized focus according to the pupil, its base direction, and amount of decentralization, were measured. A total of 505 (50.4%) of the subjects were female and 497 (49.6%) were male. The mean age was 37.0 (range 3-81). The mean PD of the subjects was 59.9 ± 4.09 mm, and mean optical center distance (OCD) of the lenses was 65.6 ± 4.07 mm. The difference between PD and OCD was significant (p < 0.001). While the right spherical, cylindrical, and axial differences and left spherical, cylindrical, and axial differences between the prescription and the spectacles were not significant, the left axial difference was statistically significant (p < 0.001). The decentralization direction was towards the lower temporal with a percentage of 76.8% on the right and 80.3% on the left lenses. The mean amount of the decentralization was 4.37 ± 2.39 mm on the right and 4.63 ± 2.36 mm on the left. Dioptric error in the spectacles was quite low. However, there may be a small amount of axis deviation at the time of mounting the lens to the frame. We conclude that asthenopic complaints due to PE caused by the decentralization of the optic center of the lenses are quite important. Examination of the spectacles after they are prepared can be deemed as a solution to reduce asthenopic complaints due to improper spectacles.